legal rules of the Kazakh Khanate and its role and importance in family and marital relations (Journal of history, 2019)
This article is about the importance and role of the statutes and laws of the Kazakh khanate in the familymarriage. At that time statutes and laws of the Kazakh khanate in connection with social’s conditions were improved and changed. The statutes and laws have decided many problems in society. The law played an important role in a peaceful and quiet life of the Kazakh people. And many an unfortunate accidents was decided fairly and favorably by the Board of governors and the judge. In this regard, the statutes and laws of the Kazakh khanate had a special respect among the people. Before the statutes and laws of the Kazakh khanate all people were equal and the fair decision of the law argued before the people. With one word from this article you can know that, in the Kazakh society statutes and laws of the Kazakh khanate was formed in ancient times.